INCREASING STUDENTS UNDERSTANDING IN CLASS VI SOCIAL STUDIES LEARNING MATERIAL THROUGH SOFT CARD STRATEGY - Elsa Agustin Subagiono; Kusnaningsih Kusnaningsih; Rika Wulandari (maktab: Jurnal Pendidikan dan Teknologi, 2022)
This study aims to increase students' understanding of social studies subjects by using strategies or soft card techniques. The research subjects were conducted on all 33 students in class VI, with 19 male students and 14 female students accompanied by the class teacher. This research is a classroom action research with the Kemmis and McTaggart models. Kemmis and McTaggart's model has four stages with two cycles. The procedure for carrying out the actions at the research location was divided into two cycles accompanied by pre-cycles. Collecting data in this study, namely by interviews, observations, documentation and tests orally during learning takes place. The results showed that the increase in students' knowledge at the pre-cycle stage of the average value of students' understanding was at an average value of 47 in the "low" category. In cycle I the value of students' understanding has increased to an average value of 77 in the "Moderate" category. In cycle 2, the increase in students' understanding is said to be valid because it has reached an average value of 92 in the "High" category. It can be concluded that Soft Card strategies or techniques can improve students' understanding of class VI on social studies at SD Negeri Banyuajah 2